Forms of COVID-19 state aid by beneficiary size in Poland in 2020 - Adam A. Ambroziak (International Journal of Management and Economics, 2022)
Lockdowns imposed by the European Union (EU) Member States produced significant consequences in the form of losses to companies, which is why the Member States decided to assist businesses from public funds. This paper aims to identify and initially assess the implementation of schemes under which coronavirus disease-2019 (COVID-19)-related state aid was granted in Poland in 2020 for different instruments and beneficiary sizes. The idea was to find out how well aforementioned schemes responded to the needs of companies affected the most by the COVID-19-inflicted crisis. To this end, statistical analysis was deployed to learn about the share of individual groups of businesses of different sizes in support instruments granted in relation with COVID-19 by type of aid. The study helped to demonstrate that Polish aid schemes approved by the European Commission in 2020 assisted mainly micro- and small-sized companies, which usually suffered from poor liquidity, by predominantly soft instruments.
Keywords: G38; H25; H32; H71; L53; 650; COVID-19 crisis; COVID-19 state aid; European Union; Poland; SMEs